Factors influencing Successful Aging among Older Adults - Basnet, Rajina; Shakya, Neelima (Journal of Nepal Health Research Council, 2023)
Background: The rapid growth of older population has enhanced the number of people at lifetime risk of enduring from chronic diseases. Successful aging is a significant phenomenon for achieving a healthy and happy life for all elderly and aging society. Methods: A descriptive cross sectional study was carried out with the objective of assessing the factors influencing successful aging. Structured interview questionnaire using Successful aging scale and Self-esteem scale was used for data collection and obtained data was analyzed using descriptive statistics and inferential statistics at 0.05 level of significance. Participants of the research were considered in this study using purposive sampling technique. Results: The findings revealed that majority of elderly respondents (73.8%) had successful aging. Successful aging was significantly associated with marital status (p-value= 0.040), family type (p-value=0.002), family annual income (p-value=0.009), presence of children as support system (p-value=0.034), negative life events in last 12 months (p-value<0.001), subjective perception of health (p-value=0.001) and ability to remember things without difficulties (p-value<0.001). Conclusions: Thus, it can be concluded that successful aging is associated with several factors. So, individual factors must be taken into consideration while implementing intervention programs in order to bring about positive aging experience among elderly. Keywords: Older adults; self-esteem; successful aging.